2009
DOI: 10.1021/la900296y
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Assisted Crystallization and Optical Properties of Uniform Microrods of Organic Dye Sudan II

Abstract: The self-assembly of uniform single-crystalline microrods of organic dye Sudan II (1-(2,4- dimethylphenyl-azo)-2-naphthol) in solution was achieved by reprecipitation with the assistance of amphiphilic block copolymer Pluronic F127. It was found that the formation of F127 micelles was favorable for the production of uniform Sudan II microrods whereas individual F127 molecules favored the formation of Sudan II fibers. The optical absorption and fluorescence emission properties of the uniform microrods were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…These include zero dimensional (0-D) spherical or tetrahedral quantum dots [16,17], one-dimensional (1-D) nano rods and wires from small organic compound [18][19][20] and two-dimensional (2-D) nanoplates [21], nanoribbons and nanotubes [22], microcapsule [23], organic nano flower [24], sub-microtube [25], etc. Various techniques were developed to prepare organic nano/ micro particle, such as reprecipitation [26], physical vapor deposition [27], microemultion [28], ultra-sonication [29], template method [30], self-organization [31], postchemistry [32][33][34][35], etc.…”
Section: Introductionmentioning
confidence: 99%
“…These include zero dimensional (0-D) spherical or tetrahedral quantum dots [16,17], one-dimensional (1-D) nano rods and wires from small organic compound [18][19][20] and two-dimensional (2-D) nanoplates [21], nanoribbons and nanotubes [22], microcapsule [23], organic nano flower [24], sub-microtube [25], etc. Various techniques were developed to prepare organic nano/ micro particle, such as reprecipitation [26], physical vapor deposition [27], microemultion [28], ultra-sonication [29], template method [30], self-organization [31], postchemistry [32][33][34][35], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al found that the elongated truncated lozenge‐shaped single crystals were formed by the self‐assembly of poly(2‐vinylpyridine)‐ block ‐poly(ε‐caprolactone) (P2VP‐ b ‐PCL) in mixed solvent. Moreover, single‐crystalline microrods of Sudan II could be prepared by self‐assembly in the solution through reprecipitation with the assistance of amphiphilic block copolymer (F127) . These examples showed that the amphiphilic block copolymers containing crystalline polymer chains were important for the preparation of well‐defined regular prism.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, aggregation-induced emission enhancement (AIEE) has been reported not only for siloles 2 and tetraarylethylenes 3 but also for dyes, such as BODIPY, 4 4-dicyanomethylene-2,6-distyryl-4H-pyrans, 5 polyenes, 6 and Sudan II. 7 Therefore, it is of significance to find new AIEE dyes. We could find that suspended monoEG derivative showed weak AIEE.…”
Section: Introductionmentioning
confidence: 99%